Modelo de Equilibrio General de Ecuador: Extensión en el Análisis del Impacto Regional - Sánchez A., Leonardo (2020)
The present work broadens the analysis of the general equilibrium model developed by Pérez and Acosta (2004) for the case of Ecuador, defragmenting the possible impact of carrying out the Free Trade Agreement (FTA) with the United States on the different regions that constitute the Ecuadorian economic system. For this purpose, on the one hand, we propose a set of multivariate analysis techniques (Clusters Analysis) in order to obtain a disjoint and balanced regional separation in line with production characteristics; and, on the other hand, we review the theory of information (Maximum Cross Entropy) inorder to estimate the regional distribution of the economic effects of the FTA or another trade setting. On the basis of these tools, we intend to extend the simulations of the general equilibrium model to regional (sub-national) dimensions, using -in an efficient manner- both the information regarding the counterfactual variations that the equilibrium undergoes, and the previous information on the regional distribution of economics flows.